The Synthesis and Spectroscopic Characterization of Structural Changes in Hydrophobic Silica Aerogels upon Encapsulation of the LCC ICCG Enzyme - Tatiana Alpízar-Rojas; Juan Diego Barboza-Carmona; Erik Butenschön; Guzel Musabirova; Erick Castellón; Jörg Matysik; Isaac F. Céspedes-Camacho (Gels, 2025)
Silica aerogels are highly porous materials known for their low density and extensive surface area, making them ideal for applications in thermal insulation, catalysis, and environmental remediation. This study investigates the structural changes of functionalized hydrophobic silica aerogels used as carriers of the LCC ICCG enzyme. The aerogels were synthesized using the sol-gel method, with trimethylethoxysilane (TMES) as a functionalizing agent to enhance hydrophobicity. The enzyme-encapsulated aerogels were characterized using hyperpolarized 129Xe NMR, 29Si NMR, nitrogen sorption analysis, TEM, contact angle measurements, and FT-IR spectroscopy to evaluate their structural and chemical properties. The results confirmed successful encapsulation of the enzyme, as indicated by changes in the pore structure and network morphology. These findings demonstrate that functionalized silica aerogels can effectively support LCC ICCG immobilization, offering a promising approach for plastic degradation applications.